Análise econômica da produção de soja e milho na safra verão, no estado do Paraná - Melo, Carmem Ozana de; Silva, Gerson Henrique da; Esperancini, Maura Seiko Tsutsui [UNESP] (My University, 2012)
Cultivation of soybeans and corn is an important activity in the state of Paraná, Brazil, generating employment, income, and foreign exchange. However, it was noted a displacement of areas for soybeans cultivation where the corn was cultivated in the first season (summer). In this context, this study aimed to analyze economically the production of soybeans and corn in the first season, assessing the risks associated with these two cultures. Using the variables of risk price and costs of production, it was possible to identify the risk main sources and their influence on net income. Results showed that the activities profitability is more sensitive to price than the costs in both activities. Soybeans also present the possibility of higher impairment when there are lower risk levels; and as the risk increases, there are more interesting returns, compared to corn. Thus, the soybean is a better alternative for producers with less risk aversion.

O cultivo da soja e do milho constitui uma importante atividade no Estado do Paraná, gerando emprego, renda e divisas. Contudo, vem-se observando o deslocamento da destinação de áreas de plantio de milho de primeira safra (verão) para a produção de soja. Nesse contexto, este trabalho se propôs a proceder à análise econômica da produção de soja e do milho de primeira safra, por meio da avaliação dos riscos associados às duas culturas. Utilizando as variáveis de risco “preço” e “custos de produção”, foi possível verificar que a rentabilidade das atividades é mais sensível ao preço do que aos custos, em ambas as atividades. Verificou-se também que a soja apresenta possibilidades de prejuízo mais alto para menores níveis de risco, e que, à medida que o risco aumenta, oferece retornos mais atraentes, em comparação com o milho. Desse modo, a soja constitui uma alternativa mais viável para produtores com menor aversão ao risco.
Economic analysis of corn and soybean production: summer crop in the State of Paraná, Brazil
Keywords: Risk analysis; Agricultural production; Income and cost of production; Production systems; Análise de risco; Produção agrícola; Receita e custo de produção; Sistemas de produção